PENGARUH DESTILASI ULANG ASAP CAIR TERHADAP PERUBAHAN WARNA GULA MERAH - Slamet Budijanto; Tubagus Bahtiar Rusbana (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2009)
ABSTRACTBrown sugar has a specificity than others. It is not only as a sweetener, but also have a low glicemic index and specific flavor. That are the reason why does the brown sugar become a prospective commodity in the global market. Palm juice is th raw material of brown sugar which is easy to fermentation when it is tapped. An alternative way to preserved the palm juice was using liquid smoke. The aim of this research was identifying the effect of additional liquid smoke with redistilation and without redistilation on the colour’s changing of brown sugar. It used Chromameter CR300 to measured colour intencity with La and b system. The result showed that additional liquid smoke with or without redistillation made the colour’s changing. The colour of brown sugar with additional redistillation liquid smoke lighter than brown sugar with additional liquid smoke without redistillation.Key words : Brown Sugar, liquid smoke, redistillation, colour.